Model Of Tourism Destination Development Tegal Case Study, Central Java - Anisatul Auliya Auliya; Farrah Farrah (Program Studi Hospitality dan Pariwisata, 2019)
ABSTRACTThe propose of this study is to produce the model that can be applied in Tegal area especially, for making Tegal city as a tourist destination choice by paying attention to the components that influence the development of this tourist destination, especially in Tegal Region, Central Java. If this model is applied, it's not only useful for tourist attraction in Tegal, Central Java, but also will have an impact for increasing the local revenue from tourist expenditure.Based on the results of the research that the Sig. (2-tailed) shows (0.000) <0.05. it can be interpreted that H0 is rejected and H1 is accepted. This means that in 0 of these studies, there is a significant relationship between the variables of tourism development (X) with tourism destination variables (Y) in Guci Hot Springs, Pantai Alam Indah (PAI), and Guciku Hot water boom. The tourism development model can focus on implementing green tourism, increasing promotional activities, and must involve many sectors (Multi-sector) because it requires cooperation from various parties such as the central and regional governments, the private sector, tourism managers, local communities and tourism associations. This study will use Purposive Sampling data collection techniques, and the respondents are visitors to tourist destinations in Tegal, Central Java. The method that will be used to find out aspects of tourism destination development is carried out through statistical calculations, then an analysis of tourist attraction development is carried out using SWOT analysis techniques.Keywords: Tourism development, tourism destination